2013
DOI: 10.1007/s12149-013-0748-y
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission mammography (PEM): reviewing standardized semiquantitative method

Abstract: PurposeTo validate semiquantitative analysis of positron emission mammography (PEM).MethodsFifty women with histologically confirmed breast lesions were retrospectively enrolled. Semiquantitative uptake values (4 methods), the maximum PEM uptake value (PUVmax), and the lesion-to-background (LTB) value (3 methods) were measured. LTB is a ratio of the lesion’s PUVmax to the mean background; LTB1, LTB2, and LTB3 (which were calculated on different background) were used to designate the three values measured. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…However, a direct comparison with literature data from North American and Japanese studies prove to be difficult because those studies used primarily PUV ratios (tumour to background) rather than absolute PUV values; e. g. (20). Our results are in line with the results reported recently by Yamamoto et al (24). In their study PUVmax values for 50 patients were 1.39± 0.70 for benign and 3.70± 2.57 for malignant lesions, which is very similar to the values reported (▶ Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, a direct comparison with literature data from North American and Japanese studies prove to be difficult because those studies used primarily PUV ratios (tumour to background) rather than absolute PUV values; e. g. (20). Our results are in line with the results reported recently by Yamamoto et al (24). In their study PUVmax values for 50 patients were 1.39± 0.70 for benign and 3.70± 2.57 for malignant lesions, which is very similar to the values reported (▶ Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the exclusive measurement of PUVmax should in principle improve the error susceptibility of the method. This has recently been verified by Yamamoto stating that due to its simplicity and reproducibility PUVmax is superior to lesion-backgroundratio (LTB) as an indicator for PEM (24).…”
Section: Discussionmentioning
confidence: 79%
“…Muller 28 suggested a threshold value of PUVmax >1.9 as predictive of malignancy based on an analysis of 108 patients. Other studies 1,27 have found it difficult to use a discriminatory threshold for predicting malignancy, although median PUVmax for malignancies was significantly greater than that for benign lesions. In the results reported by Narayanan et al 7 , the median PUVmax for benign lesions was 1.0 (SD, 0.4); for high-risk lesions, 1.3 (SD, 0.4); for DCIS, 1.1 (SD, 0.9); and for invasive malignancies with or without DCIS, 1.4 (SD, 0.6); p = 0.001 for differences among groups, but there was substantial overlap with some fibroadenomas, fat necrosis, and atypical hyperplasias showing intense FDG uptake.…”
Section: Quantificationmentioning
confidence: 82%
“…Although Wang et al 25 have reported a high to moderate correlation between SUV and PUV in breast tissue, the PUV value differs from SUV in absolute value because PEM images do not have corrections for attenuation or scatter. The maximum PUV for a region of interest (PUVmax) has been shown to be superior to other quantitative measures such as lesion to background (LTB) ratio for differentiating between benign and malignant tissue due to the simplicity and reproducibility of PUVmax 27 . Muller 28 suggested a threshold value of PUVmax >1.9 as predictive of malignancy based on an analysis of 108 patients.…”
Section: Quantificationmentioning
confidence: 99%
“…PUV max values for high grade carcinomas were greater than those of lower grade cancers and were higher for triple negative breast cancers than for HER2/Neu-receptor positive or estrogen-receptor positive cancers. No specified threshold for malignancy exists, although a recent study comparing LTB and PUV max recommended the use of PUV max due to its simplicity and reproducibility 26 . Another study 27 evaluated PUV max and LTB using healthy tissue in the contralateral breast as background and found that both PUV max and LTB were significantly higher for tumors compared to benign lesions.…”
Section: Imaging Techniques and Interpretationmentioning
confidence: 99%